Q#: Enabling scalable quantum computing and development with a high-level domain-specific language - Svore, Krysta M.; Geller, Alan; Troyer, Matthias; Azariah, John; Granade, Chris; Heim, Bettina; Kliuchnikov, Vadym; Mykhailova, Mariia; Paz, Andres; Roetteler, Martin (https://arxiv.org/abs/1803.00652, 2018)
Quantum computing exploits quantum phenomena such as superposition and entanglement to realize a form of parallelism that is not available to traditional computing. It offers the potential of significant computational speed-ups in quantum chemistry, materials science, cryptography, and machine learning. The dominant approach to programming quantum computers is to provide an existing high-level language with libraries that allow for the expression of quantum programs. This approach can permit computations that are meaningless in a quantum context; prohibits succinct expression of interaction between classical and quantum logic; and does not provide important constructs that are required for quantum programming. We present Q#, a quantum-focused domain-specific language explicitly designed to correctly, clearly and completely express quantum algorithms. Q# provides a type system, a tightly constrained environment to safely interleave classical and quantum computations; specialized syntax, symbolic code manipulation to automatically generate correct transformations of quantum operations, and powerful functional constructs which aid composition.